City versus countryside in Mao's China negotiating the divide - Brown, Jeremy 1976- (Cambridge University Press, 2012)
"A powerful work of grassroots history showing how China's rural-urban divide can be traced back to the policies of Mao Zedong, which pitted city dwellers against villagers"--Provided by publisher.